THE SYMBOLIC INTERACTIONISM THEORY: A SYSTEMATIC LITERATURE REVIEW OF CURRENT RESEARCH - Siti Som Husin; Anis Amira Ab Rahman; Dzulkifli Mukhtar (INTERNATIONAL JOURNAL OF MODERN TRENDS IN SOCIAL SCIENCES (IJMTSS), 2024)
The objective of this paper is to explore the current trend of using symbolic interactionism as an underpinning theory by revealing the gaps in the elements of the theory, methodology, and suggesting the direction for future research. This communication theory is unique because of the elements; self, society, and the environment. Normally, symbolic interactionism theory (SIT) has been used in identity and healthcare studies. While studies using this theory in entrepreneurship are still lacking. It is shown that this study mostly focuses on the sociology perspective compared to the social-psychology perspective. Therefore, this paper was adopted with a thematic analysis of 116 articles using symbolic interactionism as a theoretical underpinning. The findings show previous research that utilised symbolic interactionism in entrepreneurship is still less. This study found that previous studies have focused more on "Looking-Glass-self" by Goffman compared to the overall perspective of self-society-environment and lack of studies focusing on the entrepreneurship field. This systematic review is expected to give understanding and knowledge to readers about SIT, theory gaps through the elements, and directions for future research to consider using symbolic interactionism as a theoretical underpinning in the entrepreneurial phenomenon.